Penerapan PHBS Dan Protokol Kesehatan Dalam Waspada Menghadapi Gelombang Ketiga Covid-19 Di Fasilitas Olahraga Kota Bandung - Deden Indra Dinata; Santi Rinjani; Meda Yuliani; Rahmat Santoso; Hani Oktafiani (Jurnal Pengabdian Pada Masyarakat, 2022)
IMPLEMENTATION OF HEALTHY LIFESTYLE AND HEALTH PROTOCOL IN AWARENESS OF THE THIRD WAVE OF COVID-19 IN BANDUNG CITY SPORTS FACILITIES. Various limitations and lack of understanding in implementing PHBS and strict procedures have become problems in the community. For example, the provision of masks for orphanages that are only waiting for donations from donors, the neglect of health procedures and the lack of public concern for the implementation of PHBS in community sports facilities, cause the need for motivation to be creative and productive while still paying attention and implementing health care programs. The purpose of these efforts is to increase knowledge about health so that later they can carry out health procedures correctly and also increase good and correct PHBS behavior. The method used is educating the application of a clean and healthy lifestyle (PHBS) and health protokols through counseling, making YouTube videos that are registered as intellectual property, providing supporting facilities and information and education communication in collaboration with health promotion officers of UPT Puskesmas Cipadung. The results showed that this activity was frequently needed by partners and really useful, seen from the increase in participants' understanding of the material presented and the implementation of health protokols in the sports facility environment.